ANALISIS TERHADAP PELAKSANAAN AQAD PEMBIAYAAN DENGAN PRINSIP MUDHARABAH PADA BANK SYARIAH DALAM KAJIAN UU NO. 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH - Abdullah Kelib; Sodikul Amin (Universitas Semarang, 2017)
The Mudharabah Financing Agreement is based on trust, with another understanding that the investor will hand over the funds to the fund managerparty after the investor is sure that the borrower of the capital both skillfully andmorally is trustworthy to manage the capital provided with his expertise and willnot manipulate the capital. However, it does not mean that in the implementationof the mudharabah agreement the fund management party is released from theguarantee system or there is third party who guarantee it. This is done in order to create justice among customers / mudharib and the bank so it can protectthemselves from the loss. The problems in this research are how the implementation of mudharabahfinancing agreement in Sharia Banks, how the Banks solve the in troublemudharabah financing in Sharia Banks, what sanction is implemented tomudharib if they break the agreement in Mudharabah financing agreement. To answer the above problems, this study uses juridical normative methodqualitatively by analyzing primary, secondary and tertiary data as well asinterview materials therefore produces the answer of each problems given. Based on the research it can be concluded that, among others, thearrangement of mudharabah financing agreement is based on the holy Al-Qur'an, Al-Hadist, National Sharia Fatwa Council of MUI, Act No. 21 Year 2008 onSharia Banking and Act No. 10 Year 1998 About Banking.